Crystal‐Size‐Induced Band Gap Tuning in Perovskite Films. Issue 39 (18th August 2021) - Ummadisingu, Amita; Meloni, Simone; Mattoni, Alessandro; Tress, Wolfgang; Grätzel, Michael
Abstract: A comprehensive picture explaining the effect of the crystal size in metal halide perovskite films on their opto‐electronic characteristics is currently lacking. We report that perovskite nanocrystallites exhibit a wider band gap due to concurrent quantum confinement and size dependent structural effects, with the latter being remarkably distinct and attributed to the perturbation from the surface of the nanocrystallites affecting the structure of their core. This phenomenon might assist in the photo‐induced charge separation within the perovskite in devices employing mesoporous layers as they restrict the size of nanocrystallites present in them. We demonstrate that the crystal size effect is widely applicable as it is ubiquitous in different compositions and deposition methods employed in the fabrication of state‐of‐the‐art perovskite solar cells. This effect is a convenient and effective way to tune the band gap of perovskites. Abstract : Energy levels of perovskite nanocrystallites depend on their size owing to quantum confinement and the concurrent yet distinct phenomenon of size‐dependent structural changes where surface perturbations template the core. This effect can aid in the design of perovskite opto‐electronic devices utilizing mesoporous layers to tailor the size of infiltrated nanocrystallites.